Retention of government-assisted refugees in designated destinations: Recent trends and the role of destination characteristics - Yasmin Gure; Feng Hou (Economic and Social Reports)
This study asks if the retention of refugees resettled in Canada as part of the Government-Assisted Refugees (GAR) in their designated destinations has increased since the early 2000s. And if so, to what extent can the change in the retention rate be accounted for by changes in refugees’ sociodemographic characteristics and the context of the designated destination, including factors such as the existence of resettlement service agencies, economic conditions, ethnic enclaves and cluster resettlement.